Unisexual infection with Schistosoma mansoni in mice has the potential to boost the immune response against eggs after challenge infection - Reinholdt, Cindy; Winkelmann, Franziska; Koslowski, Nicole; Reisinger, Emil C.; Sombetzki, Martina (Frontiers in Immunology, 2023)
The complexity of the Schistosoma spp. life cycle and their effective immune evasion strategies, makes vaccine development challenging. Unisexual infection models, that excludes any immunomodulatory effects of the parasite eggs, may contribute to a better understanding of complex immunological processes and identification of new targets for vaccine research. We have recently shown that long-term unisexual infection with schistosomes in mice results in an unpolarized Th1/Th2 response associated with an abnormally enlarged spleen and diffuse liver inflammation. Herein, we investigated whether (i) unisexual worms can mate after three months of single sex infection and (ii) thus the Th2 response induced by oviposition can reverse or heal the described systemic inflammation. Therefore, we infected 6–8 weeks old female C57BL/6J mice with 100 male or female cercariae and reinfected with the opposite sex for the same period after 12 weeks. At 24 weeks after initial infection, we histologically examined worm mating, as evidenced by the presence of parasite eggs, infection-related pathology associated with eggs, and characterization of fibrosis in the livers. Single worms are able to mate months after unisexual infection and start oviposition. Egg deposition has been associated with a typical Th2 immune response in the liver after unisexual reinfection, accompanied by increased recruitment of CD4+ T cell immune cells. Hepatic collagen levels were significantly increased in the reinfected groups compared to the naive and unisexually infected group. Our results indicate that the eggs are able to restore the Th1/Th2 immune balance of a previous unisexual infection. However, the organ damage caused by the unisexual worms does not subside, but rather provides the baseline for the emerging egg-triggered inflammation and fibrosis. Since single schistosomes can mate even several weeks after unisexual infection and then accumulate worm- and egg-related organ damage, infection status without positive egg detection is very important, especially in areas with low prevalence.